(untitled) (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2025)
In the 1960s, Zalman Aran was among the leading members of the labor movement. He identified the need to address social inequality as an urgent task that could no longer be postponed. His efforts, along with those of his compatriots, to expand the right to secondary education and to promote integration reflected a political agenda seeking to narrow social gaps. This aligned with the broader shift in Israel’s welfare policy at the end of the decade. The article analyzes this shift in secondary education, shaped in those years by a series of policy decisions, ad hoc committees, and Knesset laws, which established the junior high school system in Israel as part of a broader structural reform. The article explains how the new structure reflected an expansion of the universal right to education, embodying the educational dimension of Israel’s welfare state at its peak. It sheds light on the broad political consensus that facilitated the rise of state secondary education, in which generations of Israelis were educated. Its central argument is that the decision to create integrative junior high schools reflected a unique politics of equality, based on a ‘leveling-down’ approach aimed at reducing disparities and fostering cross-ethnic and cross-class encounters. This was to be accomplished not only by strengthening weaker students but also by limiting the advantages of stronger students within the public education system. The article delves into the protocols of the Rimalt Committee and for the first time sheds light on the debate surrounding the ‘leveling-down’ approach, which despite its importance has not received significant attention in previous research.